2017
DOI: 10.3906/sag-1507-185
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis-associated changes in serum levels of interferons and chemokines

Abstract: Background/aim: The aim of the study was to evaluate the serum concentration of main chemokines and interferons in patients with diagnosed endometriosis. Materials and methods:A total of 160 women were divided in two study groups (group 1 -endometriosis; group 2 -healthy women).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
(40 reference statements)
3
6
0
Order By: Relevance
“…Unfortunately, IL-8 was excluded in the present study due to technical problems. Previous studies have reported significantly lower concentrations of the closely related CXCL9 and CXCL10 (also called IP-10) in peripheral blood in endometriosis [18,19,20], in line with the present study. There is increased expression of MMP-9 in endometrium [21] and in peritoneal fluid in endometriosis [22], and MMP-9 cleaves CXCL9 at three different sites and degrades CXCL10 [23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Unfortunately, IL-8 was excluded in the present study due to technical problems. Previous studies have reported significantly lower concentrations of the closely related CXCL9 and CXCL10 (also called IP-10) in peripheral blood in endometriosis [18,19,20], in line with the present study. There is increased expression of MMP-9 in endometrium [21] and in peritoneal fluid in endometriosis [22], and MMP-9 cleaves CXCL9 at three different sites and degrades CXCL10 [23].…”
Section: Discussionsupporting
confidence: 93%
“…We could not find any studies regarding the impact of menopause on the proteins that differed the most. Generally, several cytokines are elevated in postmenopausal women, e.g., IL-1β, IL-6, and IL-8, which is why the actual estimated differences may be underestimated [20,33,34]. The phase of the menstrual cycle was neither known in controls nor in endometriosis, but the majority of endometriosis patients were on continuous hormonal treatment affecting the cycle.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ is also expressed at elevated levels in ectopic endometrium in contrast to eutopic endometrium of patients with endometriosis; a similar situation is observed in serum as well as in peritoneal fluid of patients (97)(98)(99), which is related with an unbalanced immune activity in endometriosis. IFN-γ is involved in increasing the resistance of endometrial cells to apoptosis and to stimulate the expression of cell adhesion molecules to allow the establishment of endometriotic lesions (99).…”
Section: Alterations Of Immune Mediatorsmentioning
confidence: 62%
“…It has been reported concentrations of RANTES to be elevated in ectopic endometrium and RANTES to correlate with the stage of the disease. Unfortunately, to date, there are not many studies investigating the relationship of serum RANTES with endometriosis [30,31]. In our attempt to bring to light the possible correlation between them, we found that RANTES levels were higher in women with endometriosis compared to controls but without statistically significant difference.…”
Section: Discussionmentioning
confidence: 67%